C THE ROLE OF THE PESANTREN ENVIRONMENT IN THE PRACTICAL APPLICATION OF RELIGIOUS KNOWLEDGE BY I’DADIYAH STUDENTS - hikmah, Rodiatul; Inayah, Badriyatil; Ma’unah, Farihatul; Thalibah, I’anatut; Lathifah, Nur Aini; Nufus, Dwi Hayatun; Wardani, Nur Laily Aprilya (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to identify supporting and inhibiting factors in managing the Islamic boarding school environment that influence student learning. The method used is qualitative with an in-depth interview approach, field observation and document analysis. The research results show that supporting factors include a structured curriculum, a conducive physical environment, strong social interaction, and family and community involvement in supporting students' learning. However, there are several inhibiting factors, such as limited learning facilities and resources, monotonous learning methods, an imbalance between theory and practice, as well as students' social and psychological problems. The recommendations provided include developing relevant curricula, improving facilities, using interactive learning methods, and providing psychological and social support. By paying attention to these factors, management of the Islamic boarding school environment can be optimized to support students in mastering and applying religious knowledge comprehensively.